Consumer perceptions on emojis: A research analysis on the impact of emojis on gen-z in social media marketing & brand image - Reunanen, Aarni Eevert (2024)
This master’s thesis studies the modern phenomenon of emoji marketing, and more specifically how the use of emojis affects the social media performance of companies inside generation z, the largest generation of users inside social media platforms.